Comparative thermal research on tetraazapentalene-derived heat-resistant energetic structures - Jing Zhou (Nature Portfolio, 2020)
Abstract Organic inner salt structures are ideal backbones for heat-resistant energetic materials and systematic studies towards the thermal properties of energetic organic inner salt structures are crucial to their applications. Herein, we report a comparative thermal research of two energetic organic inner salts with different tetraazapentalene backbones. Detailed thermal decomposition behaviors and kinetics were investigated through differential scanning calorimetry and thermogravimetric analysis (DSC-TG) methods, showing that the thermal stability of the inner salts is higher than most of the traditional heat-resistant energetic materials. Further studies towards the thermal decomposition mechanism were carried out through condensed-phase thermolysis/Fourier-transform infrared (in-situ FTIR) spectroscopy and the combination of differential scanning calorimetry-thermogravimetry-mass spectrometry-Fourier-transform infrared spectroscopy (DSC-TG-MS-FTIR) techniques. The experiment and calculation results prove that the arrangement of the inner salt backbones has great influence on the thermal decompositions of the corresponding energetic materials. The weak N4-N5 bond in “y-” pattern tetraazapentalene backbone lead to early decomposition process and the “z-” pattern tetraazapentalene backbone exhibits more concentrated decomposition behaviors.